ONLINE HEALTH CONSULTATION PLATFORM DURING THE COVID-19 PANDEMIC - Budi Santoso; Siti Fazzaura Putri Sarahdeaz; Hertanti Indah Lestari; Yudhie Tanta (Fakultas Kedokteran Universitas Sriwijaya, 2021)
Indonesia is currently experiencing the second wave of the Covid-19 pandemic. The Coronavirus is currently spreading faster with a higher severity, causing an increase in Covid-19 cases in the UNSRI Medical Faculty. There were 73 students and 13 lecturers and/or educators who were confirmed to have Covid-19 as of July 14, 2021, who had been recorded since early July. The increase in the number of confirmed cases of Covid-19 in students and lecturers causes the teaching and learning process to be suboptimal. . In addition, the increasing number of Covid-19 in the community while access to hospitalization is reduced, causing many people to need to self-isolate at home, who need a consultation about their health.The need for online health services is currently increasing as well where the Covid-19 number is currently at its peak. Many people need self-isolation at home because hospitals lack treatment facilities. Online health services are needed by people who find it difficult to consult directly with health facilities.The Faculty of Medicine, Sriwijaya University (FK Unsri), especially the lecturers who are also health workers, initiated the formation of the Online Doctor Chat (CDO), as a response to the Covid-19 pandemic situation